P–083 Analysis of chromosomal segregation and interchromosomal effects (ICE) in sperms from balanced translocation carriers using fluorescence in situ hybridization (FISH) after sperm selector separation. (6th August 2021) - Machowetz, A; Shebl, O; Maurer, M; Ebner, T; Duba, H C
Abstract: Study question: Influence of sperm selector separation of sperms on their translocation load, segregation pattern, motility and occurrence of interchromosomal effects Summary answer: Sperm selector separation led to reduction of the translocation load, shift in segregation pattern and lower rates of interchromosomal effects within sperm samples What is known already: Balanced translocations in men are known to be one of the main causes of reproductive failure. The segregation pattern in sperms is determined by the distribution of the chromosomes during meiosis. Interchromosomal effects can also influence the distribution of chromosomes that are not involved in the translocation. The sperm selector used consists of two concentric chambers, which are overlaid by a U-ring and a cover glass. Motile sperms migrate from the native ejaculate in the medium filled inner chamber by using a capillary bridge created by the U-ring. This avoids potential harmful centrifugation and allows accumulation of motile sperms. Study design, size, duration: Twenty-one carriers of balanced translocations participated in the study. In addition, 15 patients were involved as control. All participants signed an informed consent (F–8–15). Samples of three patients did not meet the internal quality criteria and had to be excluded from analysis. The study started in 2015 and is still ongoing. Participants/materials, setting, methods: Liquefied native ejaculate was processed with a sperm selector. Native ejaculate, non-migrated sperms from the outer chamber and migrated sperms from the inner chamber were transferred onto glass slides, fixed and underwent a decondensation treatment. For segregation analysis FISH translocation specific FISH probe mixes were used and tested on patient's blood. Interchromosomal effects were analysed with FISH probes for the chromosomes X, Y, 18 and 13, 21. Evaluation was done manually using fluorescence microscopy. Main results and the role of chance: Segregation analysis was done for more than 25, 000 sperms from men carrying a balanced translocation (18 patients with reciprocal and 3 patients with Robertsonian translocation). Separation via sperm selector led to a reduction in translocation load (native to separated approach 49, 1±11, 5% to 34, 8±9, 4% (P = <0, 01), the rate depending on the specific translocation. There was also a shift in the segregation pattern, which seemed to be influenced by the specific translocation and the resulting steric alignment of the corresponding quadrivalent / trivalent. Additionally, more than 90, 000 sperms from patients with balanced translocations were analysed for interchromosomal effects. Separation led to reduced maldistribution rate (native to separated approach 7, 1±3, 5% to 5±3, 1%, P = <0, 01) whereas the steric alignment of the corresponding quadrivalent / trivalent seems to influence the interchromosomal effect as well. For control, sperms from control patients were analysed regarding the chromosomes X, Y, 18 and 13, 21. In about 90, 000 control sperms separation led to reduced maldistribution rate (native to separated approach 5, 4±1, 5% to 3, 8±1, 1%; P = <0, 01). Limitations, reasons for caution: The number of accumulated strandbreak-free sperms depended on the motility and sperm count of the native ejaculate. Examinations are not reproducible, as each sample delivery is influenced by external circumstances Wider implications of the findings: Sperm selector separation can be used before ART to reduce the translocation load and rate of maldistribution in sperms from carriers of balanced translocations. This could have a considerable impact on PGT results after trophectoderm biops. Trial registration number: Not applicable